Hydroxyapatite and bone particle-doped ceramic water filters for the removal of fluoride and bacteria. Issue 1 (31st December 2022) - Omoniyi, Oluwole A.; Salifu, Ali A.; Obayemi, John D.; Oyewole, Oluwaseun K.; Nigay, Pierre-Marie; Akin-Ojo, Omololu; Soboyejo, Winston O.
Abstract: This paper examines the effects of hydroxyapatite (HA) and bone-particle (BP) doping on the removal of fluoride and bacteria by ceramic water filters (CWFs). The CWFs were produced by mixing clay, sieved sawdust, and either HA or BPs in a weight ratio of 30:50:20 and sintered at 850°C or 900°C to produce micro-/nano-porous structures that remove microbial pathogens (by geometric occlusion) and fluoride (by adsorption) from contaminated water. The HA-doped filters exhibited similar flow characteristics to the BP-doped filters. However, BP-doped CWFs were more effective in removing fluoride and microbial pathogens (such as E. coli ) from contaminated water than HA-doped filters. The water flow rates and fluoride removal depended on sintering temperature, with CWFs sintered at 850°C enabling faster flow rates of 2.2Lh −1 and higher fluoride removal of 2.74 mol.cm −2 than the CWFs sintered at 900°C. Fluoride removal by the HA- and BP-doped filters was well characterized by Freundlich isotherms that reveal the occurrence of spontaneous but heterogeneous adsorption. The implications of the results are discussed for the design of point-of-use CWFs for the removal of fluoride and microbial pathogens.